Music sheet do not go gentle into that good night (2016), for four narrators and mixed choir, on a poem by Dylan Thomas (2018)
SHEET DO NOT GO GENTLE INTO THAT GOOD NIGHT (2016) FOR FOUR RECYCLERS AND MIXED CHORUS ON A POEM BY DYLAN THOMAS